Wisdom in the Funerary Inscription of Demas at Leontopolis: A Lexical Analysis of σοφία in Hellenistic Jewish Sources - Askin, Lindsey A. (Henoch, 2021)
A Hellenistic epitaph from Leontopolis (JIGRE 30; IM 14; CPJud 1490) describes its owner Demas as having helped many by his “wisdom”: σο̣φ̣[...], usually reconstructed as σο̣φ̣[ίαι]. However, the inscription is silent about Demas’ occupation: debated as scribe, physician, or magistrate. This article explores, through lexical analysis, on what basis may sophía be reconstructed, what might the epithet say about Demas’ occupation, and what might Demas’ sophía reveal about Hellenistic Jewish wisdom in general. The most plausible reconstruction is found to be σο̣φ̣[ίαι], with alternatives being semantic equivalents. It is also found that Demas’ wisdom has much in common with texts like Proverbs, Ben Sira, 4QInstruction, and Greek sources, including papyri. However, discovering Demas’ occupation is arguably less certain, even if sophía is likely. Demas’ epitaph casts doubt on the notion that wisdom is usually restricted to Jewish scribes, sages, and elites. Lastly, it is proposed that inscriptions and other documentary sources may better contextualise the meaning of wisdom, and other terms, in late Second Temple Judaism.